The Promise of American Pentecostal Political Theologies - Studebaker, Steven M. (Pneuma, 2022)
Political strife and cultural upheaval characterize public life in the United States today. When did it start? Not with Donald J. Trump’s election, but he certainly amplified and accelerated these trends. Do the Spirit of Pentecost and communities of people filled with and empowered by the Holy Spirit offer a way forward beyond the acrimony, hatreds, bigotries, and political polarities? The articles in this issue think they do. With these concerns and questions in mind, the articles presented here assess, critique, and offer constructive proposals for pentecostal political theology and practice in the age of Trump and beyond. This introductory article lays groundwork, historical and theological, for the generative contributions these articles make to pentecostal political theology in the United States.